Opportunities and limitations of shared decision making in multidisciplinary tumor conferences with patient participation – A qualitative interview study with providers. Issue 4 (April 2021) - Bohmeier, Barbara; Schellenberger, Barbara; Diekmann, Annika; Ernstmann, Nicole; Ansmann, Lena; Heuser, Christian
Highlights: Shared decision making in tumor conferences with patients seems to be challenging. Patients are typically presented one treatment option and their benefits and risks. Patients can potentially ask questions and contribute individual information. Patients have the opportunity to state their preferences to the recommendation. Discussions cover the presented option, but not alternative treatment options. Abstract: Objective: The aim of this study was to examine opportunities and limitations of shared decision making in multidisciplinary tumor conferences with patient participation from the providers' perspective in breast and gynecological cancer centers. Methods: Semi-structured guideline-based expert interviews were conducted with providers from breast and gynecological cancer centers with and without patient participation in multidisciplinary tumor conferences. Interviews were transcribed, anonymized and analyzed using qualitative content analysis. Results: The providers (n = 30) reported that some process steps of shared decision making can be implemented in limited form and under certain conditions in multidisciplinary tumor conferences with patient participation. Above all, patients can potentially ask questions and contribute individual additional information and their preferences. Conclusion: This study contributes first insights into the implementation of shared decision making in multidisciplinary tumor conferences with patient participation. From the providers' perspective, the implementation of shared decision making seems difficult under the current circumstances. Further studies, using patient experiences, participative observations or interventional designs, are required. Practice Implications: Despite the limited implementation of shared decision making in tumor conferences, patient participation can be advantageous as it can allow patients to ask questions and contribute individual additional information as well as their preferences.